2003
DOI: 10.1074/jbc.m302429200
|View full text |Cite
|
Sign up to set email alerts
|

α-Helical Coiled-coil Oligomerization Domains Are Almost Ubiquitous in the Collagen Superfamily

Abstract: ␣-Helical coiled coils are widely occurring protein oligomerization motifs. Here we show that most members of the collagen superfamily contain short, repeating heptad sequences typical of coiled coils. Such sequences are found at the N-terminal ends of the C-propeptide domains in all fibrillar procollagens. When fused C-terminal to a reporter molecule containing a collagen-like sequence that does not spontaneously trimerize, the Cpropeptide heptad repeats induced trimerization. C-terminal heptad repeats were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 66 publications
2
78
0
Order By: Relevance
“…7, which is published as supporting information on the PNAS web site, potential interhelical g Arg to eЈ Glu salt bridges are found in many other short (15-50 aa in length) parallel trimeric coiled-coil domains of intracellular, extracellular, transmembrane, viral, and synthetic proteins. Several members of these autonomous coiled coils are well characterized (9,30,31,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Based on the alignment, the sequence motif R 1 -h 2 -x 3 -x 4 -h 5 -E 6 can be deduced (R ϭ Arg; E ϭ Glu, L ϭ Leu; h 1 ϭ Ile, Leu, Val, Met; h 2 ϭ Leu, Ile, Val; x ϭ any amino acid residue).…”
Section: The Sequence Motif R-h-x-x-h-e Is Conserved Among Parallel Tmentioning
confidence: 99%
“…7, which is published as supporting information on the PNAS web site, potential interhelical g Arg to eЈ Glu salt bridges are found in many other short (15-50 aa in length) parallel trimeric coiled-coil domains of intracellular, extracellular, transmembrane, viral, and synthetic proteins. Several members of these autonomous coiled coils are well characterized (9,30,31,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Based on the alignment, the sequence motif R 1 -h 2 -x 3 -x 4 -h 5 -E 6 can be deduced (R ϭ Arg; E ϭ Glu, L ϭ Leu; h 1 ϭ Ile, Leu, Val, Met; h 2 ϭ Leu, Ile, Val; x ϭ any amino acid residue).…”
Section: The Sequence Motif R-h-x-x-h-e Is Conserved Among Parallel Tmentioning
confidence: 99%
“…In nature, α‐helical bundles such as helix‐loop‐helix (HLH) and helix‐turn‐helix motifs are frequently observed in coiled coil proteins 16. The antiparallel LK dimer has a close resemblance to that of natural HLH motifs with the exception of the fact that the monomeric units in the dimer are linked via disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested two separate motifs important for the correct folding of collagen type XIII: one region in the NC1 domain and one in the NC3 domain (38). These motifs are conserved in collagen types XXIII and XXV and have therefore been suggested to be of importance also for these transmembrane collagens (38,39). In accordance with a previous report (18), CLAC formed dimers and trimers even though the splice variant expressed in this study lacks parts of the sequences of the COL3 and NC4 domains (residues 589 -640, according to the numbering of GenBank TM /EBI accession number AF293341).…”
Section: Discussionmentioning
confidence: 99%